COVID-19 breakthrough infections and humoral immune response among BNT162b2 vaccinated healthcare workers in Malaysia - Su Lan Yang; Adiratna Mat Ripen; Chin Tho Leong; Jen Ven Lee; Chia How Yen; Avinash Kumar Chand; Karina Koh; Nur Aisyah Binti Abdul Rahim; Varaalakshmy Gokilavanan; Nik Nur Eliza binti Mohamed; Raj Kumar A/L. Sevalingam; Nadirah Sulaiman; et al. (Emerging Microbes and Infections, 2022)
The evaluation of breakthrough infection and humoral immunity responses are important outcomes for vaccination policy for healthcare staff. This prospective cohort study collected blood samples at 5-time points; before primary vaccine doses, and at 2, 10 and 24 weeks after BNT162b2 vaccination from 551 HCWs, between March and October 2021. We investigated the association between anti-spike-1 protein receptor-binding domain (anti-S1-RBD) antibody geometric mean titre (GMT) and breakthrough infections. Two weeks post-vaccination, the GMT of anti-S1-RBD antibodies was measured at almost maximum detectable value (3115 BAU/ml [95% CI, 3051–3180]); it decreased to 1486 BAU/ml (95% CI, 1371–1610) at 10 weeks; and to 315 BAU/ml (95% CI, 283–349) at 24 weeks. Prior COVID-19 infection and age significantly affected the antibody titres. Fifty-six participants, none of whom were COVID-19 convalescents, had breakthrough infections between 10 and 24 weeks post-vaccination. Before breakthrough infections, the GMT was not different between the breakthrough and non-breakthrough individuals. After infection, the GMT was significantly higher in individuals with breakthrough infections (2038 BAU/ml [95%CI, 1547–2685]), specifically in symptomatic breakthroughs, compared to those without infection (254 BAU/ml [95%CI, 233–278]). A notable surge in breakthrough infections among healthcare workers coincided with the emergence of the Delta variant and when BNT162b2-elicited antibody responses waned in 10–24 weeks (i.e. approximately 3–6 months). Post-breakthrough, the antibody response was boosted in individuals with symptomatic presentations, but not asymptomatic individuals. The study finding supports administering booster vaccination for healthcare staff, including those who recovered from asymptomatic breakthrough infection.